Heterosis and heritability of traits contributing to select high yielding drought stress tolerance sweetpotato breeding lines - Mahaman Mourtala Issa Zakari; Emeka Benjamin Utobo; Zangui Souley Moussa; Josefina Ndamononghenda Abed; Ifeanyi Maxwell Nwankwo Innocent; Happiness Ogba Oselebe (Cogent Food & Agriculture)
Exploiting heterosis in sweetpotatoes is key to developing high-performance hybrids. The objective of this study was to estimate the heterosis and heritability of traits that contribute to drought stress tolerance and storage root yield in sweetpotatoes. Experiments were conducted at six locations in Niger (Kollo, Kalapate, Bengou, and Bangui) and Nigeria (Abakaliki and Umudike). Data were collected on storage root yield and its components as well as drought parameters. Statistical analysis was performed using SAS software. The combined ANOVA results revealed a highly significant difference (p < 0.001) between genotypes and genotype × location interactions for all traits across the six locations under both water regimes. Five hybrids (5 × 12-1 with 108.06%, 6 × 8-5 with 98.31%, 7 × 6-1 with 131.00%, 8 × 6-1 with 91.14%, and 12 × 5-1 with 115.33%) under drought and three (6 × 13-1 with 52.90%, 7 × 6-1 with 200.20%, and 8 × 6-1 with 83.25%) under normal conditions showed positive significance (p < 0.05) or high positive significance (p < 0.01) BPH for storage root yield (SRY). Other hybrids showed heterobeltiosis in chlorophyll content, canopy temperature, and dry matter content under both conditions. Highly significant (p < 0.01) and strong positive genotypic and phenotypic associations were obtained between chlorophyll content and upper biomass yield (0.87) and between storage root diameter and storage root yield (0.81). The study recommended that (1) hybrids 5 × 12-1, 6 × 8-5, 7 × 6-1, 8 × 6-1, and 12 × 5-1 are good for SRY under drought conditions; (2) hybrids 6 × 8-5 and 11 × 7-1 are recommended for vines production under rainfall to feed animals; and (3) hybrids 3 × 12-3 and 12 × 5-1 with high dry matter content are recommended for industrial used.